OpenVIVO: Transparency in Scholarship - Ilik, Violeta; Conlon, Michael; Triggs, Graham; White, Marijane; Javed, Muhammad; Brush, Matthew; Gutzman, Karen; Essaid, Shahim; Friedman, Paul; Porter, Simon; Szomszor, Martin; Haendel, Melissa Anne; et al. (Frontiers in Research Metrics and Analytics, 2018)
OpenVIVO is a free and open hosted semantic web platform open to anyone that gathers and shares open data about scholarship around the world. OpenVIVO, based on the VIVO open source platform, provides transparent access to data about the scholarly work of its participants. OpenVIVO demonstrates the use of persistent identifiers, automatic real-time ingest of scholarly ecosystem metadata, use of VIVO-ISF and related ontologies, attribution of work, and publication and reuse of data – all critical components of presenting, preserving, and tracking scholarship. The system was created by a cross-institutional team over the course of three months. The team created and used RDF models for research organizations in the world based on Digital Science GRID data, for academic journals based on data from CrossRef and the US National Library of Medicine, and created a new model for attribution of scholarly work. All models, data, and software are available in open repositories.